The auto assist bar system for disabled people - Alimi, Zainal Abidin (2015)
This paper presents the development of the auto assist bar system to help the disabled people especially paralyzed in the legs where they have a problem to doing transaction stand-to-sit and sit-to-stand. An example the difficult movement of people with disabilities are from wheelchair to bed or from wheelchair to the toilet bowl. Many people with disabilities use the grab bars or assist bar are sold in the markets where it is too difficult and require a lot of energy to use which can cause them to fall and injured. Through this system, the disabled people can do the transaction stand-to-sit and sit-to-stand without assistance from other persons. The work will be performed during this project is testing performance of the sensors, design for the entire system either on mechanical parts and use the PID controller by using Arduino to control of dc motor. PID parameter values of Kp, Ki and Kd is obtained which is suitable to enable a dc motor rotates smoothly. The overall results obtained from this project found all managed to achieve the overall objectives of the system where the system is able to support people with disabilities to stand up and sit down.